Past, Present and to Come. Some Reflections on Teacher Education in Scotland - James Scotland; Yvonne Bain (University of Aberdeen, School of Education, 2016)
Jimmy Scotland, was formerly a Principal of Aberdeen College of Education. He died in 1983 - just weeks before he was due to retire. His reflective article on the teacher education system in Scotland was written for the 1983: volume 20 edition of Education in the North. It offers an interesting insight into the concerns of teacher education at the time of change: financial cuts, college mergers (or closures), changes in the BEd and other courses as a result of "new curricular and new technology" and an increased emphasis on distance learning to meet the changing professional development demands - so not too far removed from the current situation in teacher education in Scotland.